Gender trouble and current archaeological debates - Matić, Uroš 1987-; Gajdarska, Biserka ca. 20./21. Jh; Coltofean-Arizancu, Laura; Díaz-Guardamino, Marta (Springer, 2024)
Chapter 1. Let’s Talk About Gender – The Place of Gender in Current Archaeological Debates (Gaydarska et al) -- Part I. New Methods, Theories and Approaches -- Chapter 2. Sex, Gender and the Third Science Revolution (Rebay-Salisbury) -- Chapter 3. Mapping Collaborations: Working in the Contact Zone of Posthumanism and Gender Archaeology (Kay and Eriksen) -- Chapter 4. Gender in Digital Archaeology in Europe and North America (Díaz-Guardamino) -- Part II. Studying Aspects of Gender in the Past -- Chapter 5. Intersectionality and Gender in Archaeology (Sterling) -- Chapter 6. Gender and Social Inequality (Bickle and Peña) -- Chapter 7. Gender and Violence in Archaeology (Matić and Jensen) -- Chapter 8. One Step Further: Reflections on Gendered Mobility Studies Through an Examination of Recent Data from European Prehistory (Reiter and Frei) -- Part III. Communicating Gender. Chapter 9. Gender Education in Archaeology (Gaydarska and Gutsmiedl-Schüman) -- Chapter 10. Trapped in Time: Gender Representation in Archaeological Museum Exhibitions in Europe (Coltofean-Arizancu and Martins) -- Chapter 11. Coda: "Oh, The Places We’ll Go": Reflections on Engendered Archaeology Moving Forward (Conkey).
26th EAA Virtual Annual Meeting, 24-30 August 2020
Keywords: Archäologie; Mobilität; Soziale Ungleichheit; Geschlecht; Vor- und Frühgeschichte; Ausstellung; Geschlechterforschung; Archaeology; Sex.; Konferenzschrift -- 2020